Considering medical students' perception, concerns and needs for e-exam during COVID-19: a promising approach to improve subject specific e-exams. Issue 1 (31st December 2022) - Ziehfreund, Stefanie; Reifenrath, Johannes; Wijnen-Meijer, Marjo; Welzel, Julia; Sauter, Fabian; Wecker, Hannah; Biedermann, Tilo; Zink, Alexander
ABSTRACT: The COVID-19 pandemic forced a rapid shift to digital strategies including e-exams in medical schools. However, there are significant concerns, predominately from student perspectives, and further data is required to successfully establish e-assessment in the medical curricula. The objective of the study was to examine medical students' perceptions, concerns, and needs regarding e-assessment to establish a comprehensive e-exam based on these and previous findings and to evaluate its effectiveness in terms of examinee perceptions and further needs. During the 2021 summer term, a cross-sectional study using qualitative and quantitative methods was conducted among all 1077 students at the School of Medicine, Technical University of Munich. They were asked to provide information regarding their characteristics, preferred exam format, e-assessment perception, concerns, and needs in an online questionnaire. Based on these findings, a pilot e-exam including an e-exam preparation for the students were established and subsequently evaluated among 125 pilot e-exam examinees under study consideration via an online-questionnaire. Of the 317 pre-exam participants (73.2% female), 70.3% preferred in-person exams and showed concerns about the technological framework, privacy, and examination requirements. Qualitative analysis showed that these concerns lead to additional exam stress and fear of failure. The 34 (79.4% female) participants who participated in the evaluation survey showed a significantly more positive e-exam perception. The fairness of the platform, the independence from an internet connection, the organization including the e-exam preparation, and the consideration of participant needs were discussed as particularly positive in the open-ended comments. In both surveys, participants requested uniform platforms and processes for all subjects. This study provides evidence for a positive, complementary role of student participation in a successful e-exam implementation. Furthermore, when establishing an e-exam format in the medical curricula, e-exam training, equal accessibility, availability offline, and all-round fairness should be considered.